THE DIAGNOSIS AND TREATMENT OF JEAVONS SYNDROME - V. N. Kulagin; N. V. Mikhailichenko (Русский журнал детской неврологии, 2015)
The authors describe their clinical case of a female patient with Jeavons syndrome, a rare type of reflex idiopathic epilepsy. By using the data of her medical history, clinical, neurological and neurofunctional studies as an example, they show the complexity of a diagnostic search, errors and difficulties in the choice of therapeutic policy. The typical clinical manifestations of Jeavons syndrome are eyelid myoclonia with absences, eyeclosure- induced seizures, and photosensitivity, which are highly resistant to antiepileptic drugs. The introduction of current neuroimaging methods has increased the degree of evaluation the etiology of Jeavons syndrome.